Integrating the international medical graduate - Julia McLaughlin; Katherine Baker; Tracy Sandell; Shirly Mathias; Subramaniam Nagasayi; Ilona Schmidt; Christopher James (Future Healthcare Journal)
Introduction: The growing utilisation of international medical graduate (IMG) doctors in the UK has uncovered a need for hospitals to establish induction programmes that harness supportive environments for these doctors to learn within the specific context of the NHS. Currently, IMGs are under-supported at local and national levels. Method: The educational team within Withybush Hospital have designed and delivered a robust IMG induction programme. The aim was to improve IMG doctors’ clinical confidence within this specific setting. Feedback generated from the induction was provided to educational supervisors (ES) on their tutees. This induction was evaluated by questionnaires for IMGs following the induction activities, and annually for educational supervisors to assess their views. Outcome: Feedback was overwhelmingly positive with reported increased confidence post sessions. 100% of educational supervisors found the feedback provided to them very useful, allowing them to identify areas that the doctor needed support in, and aiding in the collaborative creation of development plans. Conclusion: NHS hospital-specific induction programmes for IMG doctors help to improve their clinical confidence and support their integration into their new role and environment. Additionally, educational supervisors value early, highly specific feedback generated from induction activities on the doctors they are supervising.